Adoecimento relacionado ao trabalho de docentes universitários da área da saúde - Freitas, Natiellen Quatrin (2015)
This study aimed to know the perception of academics of the courses in the health area about the illness related to their work. It is an exploratory study, descriptive, with qualitative approach. The scenery of the data collection was the Center of Health Sciences from Federal University of Santa Maria and the participants were the academics of the undergraduate courses. 13 academics from the courses in the health area participated in two steps of the research. The instruments of the data collection were a questionnaire of socio-demographic data collection and the semi structured interview. The analysis of the data derived from the questionnaire was based on the use of simple descriptive statistics and for the interviews we used analysis of the content. The research was developed in the period between April and September, 2014, after the approval by the Committee on Ethics in Research. In relation to the socio-demographic and labor results the majority of the academics are female, married or with a partner, with average age of 47 and with children. In relation to the titles, they present doctorate; with average time of 15.38 years performing in university teaching and with work regime of 40 hours with exclusive dedication. In relation to the teaching work, it was revealed the multiple dimensions that have been permeating the exercise of this profession in the university, characterized by the burden coming from the accumulation and intensification of the tasks. The context reveals itself challenging in front of the diary demands, with possibilities of repercussions in the health of the worker, from the situation experienced in the context of work. In relation to the experiences associated to the teaching work, we identified the interference of the work, permeated by the excess of activities, in the life of these individuals, reflecting in complaints of the workers. This scenery presents itself by the necessity of using alternative schedule to account for the imposed demands, as for the living with the families of the impaired. We highlight the coexistence of pleasure and suffering in the work associated to the students and to the conditions and organization of the work, respectively. With respect to the illness of the teachers, the theme is comprehended in a single way by the workers, revealing signs and symptoms presented in the life of the teachers and diseases linked to the exercise of the profession. We identify the presence of factors that the teachers are exposed at work, which are considered threatening to health, referring them to the conditions of work, interpersonal relations and work overload as the main ones. We believe that this study is going to contribute in future researches in the area, as well as in the inception of the acting of the nurse in different sceneries, being one of them directed to the field of the academics of the courses in the health area, with the possibility of elaboration of alternatives that promote improving in the context of work of these individuals and the health of them.